A Confined Replacement Synthesis of Bismuth Nanodots in MOF Derived Carbon Arrays as Binder‐Free Anodes for Sodium‐Ion Batteries. Issue 16 (17th June 2019) - Zhang, Yifang; Su, Qiong; Xu, Wenjie; Cao, Guozhong; Wang, Yaping; Pan, Anqiang; Liang, Shuquan
Abstract: The inferior tolerance with reversible accommodation of large‐sized Na + ion in electrode materials has plagued the adaptability of sodium‐ion chemistry. The sluggish diffusion kinetics of Na + also baffles the desirability. Herein, a carbon fiber supported binder‐free electrode consisting of bismuth and carbon composite is designed. Well‐confined bismuth nanodots are synthesized by replacing cobalt in the metal–organic frameworks (MOF)–derived, nitrogen‐doped carbon arrays, which are demonstrated with remarkable reversibility during sodiation and desodiation. Cobalt species in the pristine MOF catalyze the graphitization around organic components in calcination, generating a highly conductive network in which the bismuth is to be embedded. The uniformly dispersed bismuth nanodots provide plenty boundaries and abundant active sites in the carbon arrays, where fast sodium storage kinetics are realized to contribute extra capacity and excellent rate performance. Abstract : Bismuth nanodots are synthesized by confined replacement reaction with cobalt from metal–organic frameworks (MOF)‐derived templates on carbon fiber substrate. As binder‐free electrode for sodium‐ion batteries, nanosized bismuth can accommodate volume changes during sodiation/desodiation. The carbon arrays are with plenty phase boundaries and abundant active sites, which can contribute to extra capacity and excellent rate performance with fast capacitive sodium storage kinetics.